Neuroethical issues in cognitive enhancement: Modafinil as the example of a workplace drug?. (February 2019) - Brühl, Annette B.; d'Angelo, Camilla; Sahakian, Barbara J.
The use of cognitive-enhancing drugs by healthy individuals has been a feature for much of recorded history. Cocaine and amphetamine are modern cases of drugs initially enthusiastically acclaimed for enhancing cognition and mood. Today, an increasing number of healthy people are reported to use cognitive-enhancing drugs, as well as other interventions, such as non-invasive brain stimulation, to maintain or improve work performance. Cognitive-enhancing drugs, such as methylphenidate and modafinil, which were developed as treatments, are increasingly being used by healthy people. Modafinil not only affects 'cold' cognition, but also improves 'hot' cognition, such as emotion recognition and task-related motivation. The lifestyle use of 'smart drugs' raises both safety concerns as well as ethical issues, including coercion and increasing disparity in society. As a society, we need to consider which forms of cognitive enhancement (e.g. pharmacological, exercise, lifelong learning) are acceptable and for which groups under what conditions and by what methods we would wish to improve and flourish.